Project-Based Learning and its Impact on the Mathematical Knowledge of 1st Year High School Students in Schools in Southern Ecuador - Orellana, Ricardo (2023)
The main principle of this research is the implementation of a didactic proposal for the teaching of mathematics, through the Project Based Learning (PBL) methodology, which is developed as a response to the challenges presented by the current curricular designs. The PBL approach is defined as a pedagogical strategy that seeks to integrate and verify the construction of individual and group knowledge for the creation, products and proposed solutions to environmental problems. The aim of this research was to intervene pedagogically in the subject of mathematics with PBL and to describe its positive effect on students with the application of a PISA-D type test. The methodology used was descriptive with a positivist approach, applied to students in the first year of secondary education in three public educational institutions in the south of Ecuador. Various evaluation instruments were used, including pre-test and post-tests, evaluating the impact of the implementation of PBL at the educational level in the mathematics class. Finally, the findings of this study allowed us to determine that PBL is an effective strategy in the learning and teaching of mathematics in secondary education.